2015
DOI: 10.1038/npjpcrm.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community-based integrated care in frail COPD patients: a randomised controlled trial

Abstract: Background:Chronic obstructive pulmonary disease (COPD) generates a high burden on health care, and hospital admissions represent a substantial proportion of the overall costs of the disease. Integrated care (IC) has shown efficacy to reduce hospitalisations in COPD patients at a pilot level. Deployment strategies for IC services require assessment of effectiveness at the health care system level.Aims:The aim of this study was to explore the effectiveness of a community-based IC service in preventing hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 45 publications
3
81
1
1
Order By: Relevance
“…Hernandez and co-authors [5, 6] found that IDM improved clinical outcomes such as survival and the number of emergency department visits, but not the number of hospital admissions. In the study by Kruis et al [7] no additional benefit of IDM compared to usual care was found, except an improved level of integrated care and a higher degree of self-reported daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…Hernandez and co-authors [5, 6] found that IDM improved clinical outcomes such as survival and the number of emergency department visits, but not the number of hospital admissions. In the study by Kruis et al [7] no additional benefit of IDM compared to usual care was found, except an improved level of integrated care and a higher degree of self-reported daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that integrated COPD care can reduce hospital admission and readmission rates, length of hospital stay, emergency department visits, mortality, disease costs, and overall fragmented care 1623. Moreover, integrated care can reduce COPD patients’ anxiety and depression and improve their health-related QoL and satisfaction 19,20,22. This could potentially be attributed to the fact that integrated care improves disease knowledge, self-management, early detection and treatment of exacerbations, and treatment adherence 19,2224…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, integrated care can reduce COPD patients’ anxiety and depression and improve their health-related QoL and satisfaction 19,20,22. This could potentially be attributed to the fact that integrated care improves disease knowledge, self-management, early detection and treatment of exacerbations, and treatment adherence 19,2224…”
Section: Introductionmentioning
confidence: 99%
“…En pacientes ingresados por agudización de EPOC, una actuación de cuidado integral basada en el desarrollo de un programa de tratamiento adaptado a las características propias de cada paciente y discutido entre el médico de primaria y el neumólogo, un taller de formación para el auto-cuidado de la enfermedad, la presencia de enfermeras de enlace entre primaria y hospital, y la posibilidad de que el paciente contactara con estas enfermeras especializadas a través de una aplicación informática consiguió reducir el número de reingresos en un 22%. Además, se consiguieron mejoras en el estado nutricional y en parámetros de auto-cuidado como el conocimiento de la enfermedad o el reconocimiento de los signos de agudización o la adherencia al tratamiento 38,[40][41][42] . En pacientes con IC que eran seguidos ambulatoriamente por una enfermera de enlace tras su ingreso también se consiguió una reducción significativa del 54 al 42% en el número de pacientes que reingresaban o fallecían, mejorando la calidad de vida y la satisfacción con la información recibida sobre la enfermedad 36 .…”
Section: Consultas No Presencialesunclassified